Shellfish abundance relationship sipetang (pharella Acutidens) and other macrozoobenthos in mangrove Forest dumai riau university marine station - Juandi, Bona; Tanjung, Afrizal; ', Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The experiment was conducted in December 2013 in the mangroves ofDumai Riau University Marine Station. The method used in this study is a surveymethod, to make observations and field sampling. This study aims to determinethe relationship of the abundance of shellfish sipetang (Pharella acutidens) withother macrozoobenthos abundance in mangrove forests Dumai Riau UniversityMarine Station. Sampling was carried out sipetang and other macrozoobenthos inplace - a place that is found sipetang, the plot (plot) measuring 1m x 1m2,amounting to 12 and sediment samples were taken at each station.Macrozoobenthos species were found in mangroves of Dumai RiauUniversity Marine Station is Telescopium telescopium, Chicoreus capucinus,Geloina coaxans, Pitar manillae, Parasesarma cf. pictum, Uca coarctata andArenicola marina. Results for the four stations sipetang abundance in mangroveforests ranged from 6.67 to 9.67 ind/m2 while other macrozoobenthos abundanceranged from 7.00 to 9.67 ind/m2. Macrozoobenthos abundance relationships andother sipetang positive and very strong where the higher the higher the abundanceof macrozoobenthos abundance of shells sipetang.Keywords: Pariaman, macrozoobenthos, Distribution